2003
DOI: 10.1046/j.0219-0494.2003.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate versus chloroquine in the treatment of rheumatoid arthritis

Abstract: Aims: The cost of treatment and monitoring of rheumatoid arthritis patients with more effective disease‐modifying drugs like methotrexate and sulphasalazine is prohibitive. This open random clinical trial was carried out with a view to assessing the status of chloroquine, the cheapest disease‐modifying drug, in the treatment of rheumatoid arthritis. Method: A total of 47 cases were included in the study. Thirty subjects were randomly assigned to methotrexate and 14 to chloroquine groups. During 6 months follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It shows a safe and effective profile not only towards malaria infection but also against autoimmune diseases such as lupus erythematosus and rheumatoid arthritis. 16,17 Also, HCQ is shown to exert activity against different diseases such as cancer, type 2 diabetes, and autoimmune disease. 18 Recently, HCQ was primitively administered to manage patients with COVID-19 infection despite several studies showing no effects of HCQ against COVID-19 as compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…It shows a safe and effective profile not only towards malaria infection but also against autoimmune diseases such as lupus erythematosus and rheumatoid arthritis. 16,17 Also, HCQ is shown to exert activity against different diseases such as cancer, type 2 diabetes, and autoimmune disease. 18 Recently, HCQ was primitively administered to manage patients with COVID-19 infection despite several studies showing no effects of HCQ against COVID-19 as compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…However, for which DMARD should be the first one, our systematic review identified six RCTs comparing the efficacy and safety between these DMARDs . Although MTX was slightly more effective than SSZ and CQ, more patients in the MTX group experienced nausea, vomiting, hepatitis, and oral ulcers. SSZ was more effective than HCQ, but it was not significant …”
Section: Recommendationsmentioning
confidence: 99%